The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1128/genomea.00122-16
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Streptococcus agalactiae Serotype Ia and III Isolates from Tilapia Farms in Thailand

Abstract: Streptococcus agalactiae serotypes Ia and III were isolated from infected tilapia in cage and pond culture farms in Thailand during 2012 to 2014, in which pathogenicity analysis demonstrated that serotype III showed higher virulence than serotype Ia. Here, we report the draft genome sequencing of piscine S. agalactiae serotypes Ia and III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…ST283 was previously reported from 17/57 (30%) GBS isolated from seven freshwater fish species, including tilapia, on sale for human consumption in Singapore in 2015: these 17 ST283 were found in only 6/586 (1%) fish from ports, but in 11/39 (28%) fish from markets [10]. Two previously reported ST283 were reported from farmed tilapia in Thailand between 2000 and 2014 [9, 25]. One ST491 and one ST1311, (a new SLV of ST491, and also a double locus variant of ST283) were isolated from tilapia in Vietnam in 2006 [9] and 2016 respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ST283 was previously reported from 17/57 (30%) GBS isolated from seven freshwater fish species, including tilapia, on sale for human consumption in Singapore in 2015: these 17 ST283 were found in only 6/586 (1%) fish from ports, but in 11/39 (28%) fish from markets [10]. Two previously reported ST283 were reported from farmed tilapia in Thailand between 2000 and 2014 [9, 25]. One ST491 and one ST1311, (a new SLV of ST491, and also a double locus variant of ST283) were isolated from tilapia in Vietnam in 2006 [9] and 2016 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas fish-associated CC7 and CC552 are geographically widespread, our literature review, up to December 2017, showed that CC283 had only been confirmed from SE Asia, although serotype III GBS had been described as the cause of disease outbreaks that occurred in 2016 in tilapia farms in Brazil [76]. Serotype III GBS isolates from Brazilian tilapia farms have now been confirmed as ST283, while this paper was in revision, and cluster with ST283 from Asia [25, 77]. This observation, in combination with import records of live Nile tilapia from Singapore to Brazil in 2014, suggests that ST283 may have been introduced into South America from Southeast Asia, underlining the potential threat of Southeast Asian ST283 to expanding aquaculture worldwide.…”
Section: Discussionmentioning
confidence: 96%
“…The outbreaks of streptococcosis have been related to environmental factors, including warm water temperatures, increased ammonia levels, and low dissolved oxygen [ 11 ]. S. agalactiae infections in tilapia have been reported in global aquaculture in different continents, especially Asia, including Thailand [ 17 , 18 , 19 , 20 , 21 , 22 ], Malaysia [ 23 , 24 , 25 , 26 , 27 ], Indonesia [ 28 , 29 ], Philippines [ 30 ], and China [ 31 , 32 , 33 , 34 ]. Importantly, the emergence of streptococcosis disease can take place anytime during tilapia farming, which may lead to the risk of disease distribution and loss of tilapia production if disease prevention and control are not well managed.…”
Section: Introductionmentioning
confidence: 99%
“…However, our understanding of the piscine GBS at the whole genome level is currently limited. Although some complete genome sequences and draft genome sequences of piscine GBS isolates have been recorded so far (Areechon et al 2016;Facimoto et WGS analysis and phenotypic characteristics has not been reported. Here, this is the rst report on draft genomes of GBS S03 and S07 isolated from Schizothorax prenanti with different pathogenicity and drugresistance.…”
Section: Introductionmentioning
confidence: 99%